Does the FT3-to-FT4 ratio easily predict the progression of NAFLD and NASH cirrhosis? - Fatih Türker (SAGE Publishing, 2021)
Background Factors causing progression from nonalcoholic fatty liver to nonalcoholic steatohepatitis (NASH) and liver cirrhosis remain relatively unknown. We aimed to evaluate the power and effectiveness of the free triiodothyronine (FT3)-to-free thyroxine (FT4) ratio to predict non-alcoholic fatty liver disease (NAFLD)/liver fibrosis and NASH cirrhosis severity. Methods Patients (n = 436) with NASH-associated liver cirrhosis (n = 68), patients with liver biopsy-proven NAFLD (n = 226), or healthy participants (n = 142) were enrolled between January 2010 and January 2020. The aspartate aminotransferase-to-thrombocyte ratio (APRI), NAFLD fibrosis score, albumin–bilirubin score (ALBI), aspartate aminotransferase (AST)-to-alanine aminotransferase (ALT) ratio, FT3-to-FT4 ratio, and Fibrosis-4 (FIB-4) were calculated and evaluated. Results All parameters were significantly higher in NASH cirrhosis than in the healthy group. Body mass index, ALT, fasting insulin, homeostatic model assessment for insulin resistance, and triglyceride levels were significantly higher in liver biopsy-proven NAFLD than in the healthy group. The APRI, NAFLD fibrosis score, ALBI, AST-to-ALT ratio, FT3-to-FT4 ratio, and FIB-4 were significantly higher in the NASH cirrhosis group than in the healthy group. In patients with biopsy-proven NAFLD, the FT3-to-FT4 ratio was significantly lower than in the healthy group. Conclusion The FT3-to-FT4 ratio is an effective and useful indicator to predict NAFLD/liver fibrosis and NASH cirrhosis severity.